Análisis jurídico y doctrinario respecto del riesgo de trabajo en caso de muerte o desaparición derivada de un acto delincuencial del trabajador. - Vásquez Quille, Carlos Andrés (2023)
The legal, doctrinal and comparative analysis regarding labor risks contemplated in the Labor Code and in the Organic Law of Public Service, is essential to guarantee the rights of workers and civil servants. The Constitution of Ecuador stipulates the rights to freedom, with the State's duty focusing on ensuring the welfare of citizens in terms of their integrity and wellbeing. As well, work is a right and a social obligation, which is why, as it is mandatory, it must be regulated in accordance with current realities in order to prevent workers or officials from becoming victims of criminal acts as a result or related to their work activities, based on the increase in criminal acts in recent years and the increase in disappearances and violent deaths associated with those acts. Also, in the current work of curricular integration, law professionals and control agents were surveyed and interviewed, resulting in suggestions for guidelines for implementing a new occupational risk in the Labor Code, the General Regulations to the Organic Law of Public Service, and the Law of Action in Cases of Missing or Lost Persons., as well as its respective compensation and implementation of a new right for missing persons, so that in this way new plans and projects of occupational safety are created.